Safety of Thrombolytic therapy at emergency department vs coronary care unit: A comparative study of 100 patients at tertiary Cardiac care centre - Sadia Saif; Rehana Khadim; Muhammad Asad; Mubarra Nasir; Mir Waqas Baloch; Urooj Alam; Farhan Tuyyab; Sumia Aslam (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2019)
Objective: To determine the safety of thrombolysis (streptokinase administration) at Emergency department with comparison to coronary care unit of AFIC and NIHD, Pakistan. Study Design: Comparative cross-sectional study. Place and Duration of Study: Emergency department and coronary care unit of Armed Forces Institute of Cardiology and National Institute of Heart Diseases Rawalpindi, Pakistan from December 2016 till May 2017. Material and Methods: All the patients with a confirmed diagnosis of acute myocardial infarction who were indicated for thrombolysis in emergency department (ER) and coronary care unit (CCU) during our study time period were included in the study through consecutive sampling. Demographic and clinical data of all patients were collected. Data was entered and analyzed in SPSS-23. Results: A total number of 100 patients were recruited in our study. The mean age of the patients was 58.18±15 years with minimum age 22 years and maximum age 85 years. Males were more in number 85 (85.0%). 64 (64.0%) patients were given streptokinase at emergency department while 36 (36.0%) were thrombolysed in coronary care unit. The most common indication for thrombolysis at ER was anterior wall myocardial infarction 24 (24.0%). The most common risk factor was smoking history (47%) followed by family history (36%). Door to needle time was smaller in emergency department in comparison with CCU [18.8±1.4 min vs 23.5±2.0 min (p=0.04)]. Major adverse cardiac events during streptokinase administration were transient hypotension, arrhythmias, hemorrhage and mortality which were minimal in Emergency Department as compared to Coronary Care Unit. Patients were immediately treated for the events accordingly both in emergency department and coronary care unit. Conclusion: Our study results yielded that thrombolysis with streptokinase was safe and effective at emergency department when compared with coronary care unit. Reducing door to needle time by considering thrombolysis at emergency department can improve the outcomes of patients.